Kesedaran Kepentingan Sisa Buangan Industri Pembinaan - Mohd Fauzi, Muhammad Adib; mohamed, sulzakimin (Research in Management of Technology and Business, 2022)
Construction waste is waste material generated from a construction project whether it involves the transportation, storage and handling of construction materials. The construction industry is one of the sectors that has a significant impact on environmental, social and economic aspects. Global warming has been a growing global concern in recent times. Global warming can cause greenhouse effects, climate change, sea level rise, acid rain and ozone layer depletion. This is because of the development of each country, it can be seen that carbon emissions have become more serious. In addition, the lack of new knowledge among contractors also causes obstacles in the use of waste to the construction industry. Therefore, the reuse of waste is very necessary. This study aims to investigate the awareness of the importance of waste in the construction industry. The objective of this study is to examine the level of awareness of developers towards the use of waste in the construction industry and to identify barriers in adapting waste in the construction industry. This study is conducted by quantitative approach. Questionnaire questions are directed to respondents in 6 firms in the state of Selangor including project managers, engineers or architects involved in the selection of materials in construction projects. The results of this study identified the high level of awareness of developers towards the use of waste in the construction industry and to study the barriers in adapting waste in the construction industry. Hopefully it can propel construction industry towards greener construction methods.